2016
DOI: 10.3389/fphys.2016.00371
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium-Sensing Receptor and the Reproductive System

Abstract: Active placental transport of maternal serum calcium (Ca2+) to the offspring is pivotal for proper development of the fetal skeleton as well as various organ systems. Moreover, extracellular Ca2+ levels impact on distinct processes in mammalian reproduction. The calcium-sensing receptor (CaSR) translates changes in extracellular Ca2+-concentrations into cellular reactions. This review summarizes current knowledge on the expression of CaSR and its putative functions in reproductive organs. CaSR was detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 122 publications
(150 reference statements)
0
18
0
Order By: Relevance
“…Intracellular pH also regulates the opening of sperm-specific Ca ++ channel (CatSper) in sperm flagella, and this is the major ion channel that regulates sperm intracellular Ca ++ . Processes such as sperm hyperactivation, capacitation, and acrosome reaction are also associated with intracellular Ca ++ fluxing through CatSper channels [ 17 , 18 ]. Pharmacological and electrophysiological studies have revealed the precise role of pH (H + ) in regulation as well as activation of CatSper channels and thereby regulation of intracellular Ca ++ .…”
Section: Ph Regulatory Mechanisms In Different Animalsmentioning
confidence: 99%
“…Intracellular pH also regulates the opening of sperm-specific Ca ++ channel (CatSper) in sperm flagella, and this is the major ion channel that regulates sperm intracellular Ca ++ . Processes such as sperm hyperactivation, capacitation, and acrosome reaction are also associated with intracellular Ca ++ fluxing through CatSper channels [ 17 , 18 ]. Pharmacological and electrophysiological studies have revealed the precise role of pH (H + ) in regulation as well as activation of CatSper channels and thereby regulation of intracellular Ca ++ .…”
Section: Ph Regulatory Mechanisms In Different Animalsmentioning
confidence: 99%
“…Recently, the CaSR PAM etelcalcetide received regulatory approval for clinical use as a more efficacious alternative for cinacalcet with a higher level of compliance (Block et al, 2017;Patel and Bridgeman, 2018;Xipell et al, 2019). CaSR expression in tissues unrelated to calcium homeostasis suggests that this receptor could also be a potential therapeutic target for cardiovascular diseases, infertility, and cancer (Ellinger, 2016;Tennakoon et al, 2016;Guo et al, 2018). Nevertheless, the precise contribution of the CaSR in these disease contexts remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…One of its physiological meaning could be that, in the female tract, different stimuli and/or ligands would be preventing premature capacitation (Figure a), the inhibition of CaSR could be a signal initiating the capacitation process (Figure b). In this regard, it has to be mentioned that a wide variety of modulators of CaSR such us calcium, magnesium, polyamines, aromatic l ‐amino acids, ionic strength, changing pH, among others (Ellinger, ; Saidak, Brazier, Kamel, & Mentaverri, ) are present in the female tract and could be modulating sperm capacitation, or even other functions as motility, through CaSR.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian gametes different studies have been carried out to elucidate the role of this receptor, demonstrating its importance in the fertilization process (Ellinger, 2016). Specifically, CaSR is implicated in bovine embryo development (Macías-García, Lopes, Rocha, & González-Fernández, 2017) and in the regulation of oocyte maturation in horses (De Santis et al, 2009) and pigs (Liu et al, 2015); additionally, it has been shown to play a role in porcine in vitro fertilization and early embryo development (Liu, Liu, Larsen, Hou, & Callesen, 2018).…”
mentioning
confidence: 99%